Weekend warrior and the risk of specific disease: a meta-epidemiology study - Keqi Fu; Jiale Wang; Hejing Pan; Lin Huang; Xuanlin Li (BMC Public Health)
Abstract Background The "Weekend Warrior (WW)" physical activity (PA) pattern, involving intensive exercise on 1–2 days per week, has become increasingly popular. The WW PA pattern demonstrates protective effects against a broad spectrum of chronic diseases; however, regarding a comprehensive investigation into the disease-specific protective mechanisms and long-term health outcomes of the subject, it remains unclear. WW exhibits protective effects against various diseases; however, there is a conspicuous scarcity of literature investigating its protective mechanisms across different disease conditions. The objective of this meta-epidemiology study was to exam WW’s protective effects by synthesizing data from published observational studies. Methods A systematic search was conducted across databases including PubMed, Embase, Cochrane Library and Web of Science through February 19, 2025. The search focused on observational studies reporting the association between the WW PA pattern and various health outcomes, including cardiovascular diseases, mortality, metabolic syndrome, and mental health, compared to inactive individuals. Odds ratios (ORs) were pooled using random-effects models. Subgroup analyses were performed to investigate the association with ORs of factors, such as sex, study type, and PA assessment. Results Twenty-seven studies encompassing 1,204,486 participants were included. The pooled analysis indicated that the WW exercise pattern significantly reduced the risk of CVD mortality (OR = 0.742, 95% CI: 0.568–0.968), I2 = 71.3%, P = 0.028). Additionally, WW showed lower risks of mental disorders and metabolic syndrome. Conclusion The WW PA pattern is associated with significant health benefits, including reduced risks of mortality, cardiovascular diseases, and metabolic syndrome. This pattern may be a viable alternative for individuals unable to engage in daily physical activity. Future research should further explore the long-term effects and refine exercise recommendations for various population subgroups. PROSPERO registration number CRD42024587216.